An uncoupled fluid structure interaction method in the assessment of structural responses of tall buildings. (June 2020) - Wijesooriya, K.; Mohotti, D.; Amin, A.; Chauhan, K.
Abstract: This paper presents an innovative and efficient numerical approach for predicting wind induced dynamic responses of a tall building. The method uses an uncoupled fluid structure interaction (FSI) approach, where wind flow data obtained from a validated Computational Fluid Dynamics (CFD) analysis was used to obtain structural responses of the 184 m tall CAARC (Commonwealth Advisory Aeronautical Research Council) building with a typical façade. An innovative method of converting recorded pressures on the building's surface, to time history nodal loads, was presented. This new method of pressure to load conversion enabled the use of an implicit modal time history analysis where the structure's dynamic behaviour was predicted. This new method was critically evaluated with a full transient structural analysis. It was shown that the proposed mapping and implicit analysis technique took 45 s to perform and was able to provide similar numerical accuracy to a full transient analysis which took 2 clock hours. Also, the proposed method was capable of predicting building responses accurately in terms of mean, maximum and standard deviation quantities of displacement where comparison were made to experimental measurements. Other important characteristics such as the impact of using higher number of modes for the proposed modal superposition method is presented and discussed.